IMPLEMENTASI PROGRAM BANTUAN PANGAN NON TUNAI (BPNT) DI KECAMATAN SITINJAU LAUT KABUPATEN KERINCI: Pebi Julianto - Julianto, Pebi (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2020)
This research took place in Sitinjau Laut Sub-District with the formulation of the problem: How is the Implementation of the Non-Cash Food Assistance Program in Sitinjau Laut District, Kerinci Regency? The aim of this research is to know and explain about the implementation of the Non Food Cash Aid Program in Sitinjau Laut District, Kerinci Regency. The research method is a qualitative with. Data collection techniques used interviews, observation, and documentation. The number of informants in this study was 19 people. The data analysis technique is data triangulation. Based on the results of research, namely the assistance provided by the government has been implemented in a structure, on target, on time and reduces the burden on the poor in terms of expenditure and can help the food security of the poor.